Physicochemical, Minerals and Antioxidant Properties of Labisia pumila var. alata of Selected Geographic Origin - M. M., Yusoff; Iwansyah, Ade Chandra (Universitas Brawijaya, 2012)
In this study, relationships between physic-chemical, mineral and antioxidant properties of water-soluble extracts of Labisia pumila var. alata are proposed. A wide range of analytical parameters were studied including physic-chemical viz., proximate composition, yield, pH, total solid, total acidity, solubility; minerals content (Ca, Fe, and Zn) and heavy metals (Cd, Hg, As, and Pb); total phenolic content (TPC), tannin content, gallic acid (GA) content, and free scavenging activity of DPPH (EC50). Data were analyzed by ANOVA and principal component analysis (PCA). Based on PCA analysis, TPC, GA content, moisture content, crude protein, and zinc content were found to have a significant positive correlation (r close to 1) to antioxidant activity. Cluster analysis (CA) resulted in four groups of L.pumila (LP). These results provide useful data about the relationships and chemical patterns in LP leaves.